Pengaruh Kepuasan Dan Citra Rumah Sakit Terhadap Kepercayaan Dan Loyalitas Pasien - Elida Eftitah; Ni Nyoman Putu Martini; Arik Susbiyani; Toni Herlambang (STIE Mandala Jember, 2023)
The hospital is an organization that provides health services carried out by professional medical personnel who are organized both from permanent medical facilities, medical services, continuous nursing care, diagnosis and treatment of diseases suffered by patients. This study aims to examine the effect of patient satisfaction and hospital image on patient loyalty with patient trust as an intervening variable. The object of this research are inpatients who seek treatment at the Fatimah Islamic Hospital in March – April 2022. The number of respondents is 100 people. The results showed: Patient satisfaction has a positive and significant effect on patient confidence in Fatimah Islamic Hospital Banyuwangi. Hospital image has a positive and significant effect on patient confidence in Fatimah Islamic Hospital Banyuwangi. Hospital patient satisfaction has a positive and significant effect on patient loyalty at the Fatimah Islamic Hospital Banyuwangi. Hospital image has a positive and significant effect on patient loyalty at the Fatimah Islamic Hospital in Banyuwangi. Patient trust has a positive and significant effect on patient loyalty at the Fatimah Islamic Hospital in Banyuwangi. Patient satisfaction has a positive and significant effect on patient loyalty which is strengthened by patient trust as an intervening variable at Fatimah Islamic Hospital Banyuwangi. Hospital image has a positive and significant effect on patient loyalty with patient satisfaction as an intervening variable at Fatimah Islamic Hospital Banyuwangi.